The MODIFICATION OF CONTROLLING SYSTEM ON CQB MK1 (CLOSE QUARTER BATTLE) ROBOT BASED ON ARDUINO MEGA 2560 USING PID METHOD - Kusumah, Andrian Anggar; Wibisono, Petrus Gunawan; Wiyanto, Suko (Jurnal Elkasista, 2021)
Abstract - PJD (close combat) in the Indonesian National Army is a battle conducted in the city and in a very large area. CQB (close quarter battle) robot is a robot to perform reconnaissance and paralyze opponents during close combat. The obstacles faced by the Indonesian National Army are city wars, wars in building areas and while conducting reconnaissance are still very lacking. From the above constraints, the author seeks to create a solution, namely by designing a mobile robot that is used to help soldiers during close combat and can use robots that are moved remotely using joysticks. In this study used experimental methods to achieve the desired results, the manufacture of this robot also has several parts that will be explained, especially in the control system that uses joysticks and elevation azimuth because of the weapon to set the position of which angle is desired for the target enemy to be aimed at based on the results of vision on the camera in the robot connected to android. By using the PID method to minimize errors and errors so that the robot can function properly.